3D design and optimization of heat exchanger network for solid oxide fuel cell-gas turbine in hybrid electric vehicles. (25th December 2019) - Tanozzi, Federico; Sharma, Shivom; Maréchal, François; Desideri, Umberto
Highlights: Solid Oxide Fuel Cell (SOFC) is considered as a range extender in hybrid vehicle. Heat Exchanger Network (HEN) to recover heat energy in SOFC system is studied. HEN synthesis is performed with a mathematical model developed in AMPL. In HEN, rectangular mini-channel heat exchangers are considered. Space optimization of HEN is performed using genetic algorithms. Abstract: The development of electric vehicles is considered as one of the sustainable way in the automotive industry to reduce greenhouse gases emissions and to allow transportation sector to comply with environmental targets required in present and future years. Due to the limited range of autonomy of the electric vehicles and the induced cost and environmental impacts of large capacity batteries, hybrid electric vehicles have been deeply investigated and developed over the last years. In this study, a Solid Oxide Fuel Cell combined with Gas Turbines (SOFC-GT) is used as a range extender in hybrid electric vehicle. The SOFC-GT system increases the autonomy of the electric vehicle and has high electric efficiency of 77%. In this work, the Heat Exchanger Network (HEN) to recover thermal energy in the SOFC-GT system has been studied. The HEN has to meet the targets of limited volume and mass to be compatible with the installation on the hybrid vehicle. This study is basically divided into three steps. In the first step, the HEN synthesis is performed with a mathematical model developed in AMPL, stating the optimal matches between hot and cold streams. In the second step, a model is developed to size the heat exchangers with the LMTD method. In the final step, an optimization problem is solved to minimize the volume or mass of the HEN, by sizing the heat exchangers with a global view of HEN, considering their assembly in a limited space and defining the paths of flow streams. Finally, some heat exchangers have been printed using plastic with a SLA 3D printer, with presentation purpose.